A dynamic voltage restorer based on voltage balanced back-to-back stacked multicell converter with equal voltage sources - Sharma G.; Kapoor A.K. (My University, 2025)
Voltage sags and swells are one of the major power quality problems in distributed system. This paper presents a dynamic voltage restorer (DVR) based on the voltage-balanced back-to-back stacked multicell converter (B2B-SMC) with equal voltage sources topology, is easy to implement, and can be easily extended for the increased number of levels. The advantages of the B2B-SMC over flying capacitor multilevel converter (FCC) and stacked multicell converter (SMC) are increased number of levels in the output voltage, low voltage total harmonic distortion (THD), lower switching losses, and reduced filter requirement. The B2B-SMC consists of two conventional stacked multicell converter (SMC), which are connected back-to-back using two low-switching frequency switches. Simulation results of a DVR based on the 17-level voltage balanced B2B-SMC are provided to validate the effectiveness of the proposed DVR topology. © 2016 IEEE.